A Strengthening Asean Cyber Cooperation in Countering Cyber Terrorist Groups Activities on the Internet by Implementing the Six-Ware Cyber Security Framework (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2018)
Nowadays, the extremism, radicalism and terrorism groups have taken advantages the use of Internet access to support their activities, i.e, member recruitment, propaganda, fundraising, cyberattack actions against their targets, etc. This is one of the issues of cyber security as a negative impact of internet utilization especially by the extremism, radicalism and terrorism groups. They know the benefits of the internet services and social media can be used to facilitate the control of information in their organizational command and control system.  In order to tackle this cyber security issue, the internet users in Association of Southeast Asian Nations (ASEAN) member countries should get more understanding as well as protection from their government against the danger of cyber extremism, cyber radicalism or cyber terrorism activities over the Internet. Therefore, this paper tries to explain the need of an ASEAN Cyber Security Framework standard in order to countering cyber terrorism activities via Internet as well as introducing the initial concept of Six-Ware Cyber Security Framework (SWCSF).